Are physical measures related to patient-centred outcomes in ARDS survivors?. Issue 10 (20th January 2017) - Chan, Kitty S; Aronson Friedman, Lisa; Dinglas, Victor D; Hough, Catherine L; Shanholtz, Carl; Ely, E Wesley; Morris, Peter E; Mendez-Tellez, Pedro A; Jackson, James C; Hopkins, Ramona O; Needham, Dale M
Abstract : Objective: To inform selection of physical measures for studies of acute respiratory distress syndrome (ARDS) survivors within 12 months of ARDS. Methods: Secondary analysis of data from 6-month survivors participating in a US multicentre prospective study (ARDSNet Long-Term Outcome Study, N=134) or a multisite prospective study in Baltimore, Maryland, USA (Improving Care of Acute Lung Injury Patients, N=99). Physical measures, assessed at 6-month follow-up, were categorised according to the WHO's International Classification of Disability and Health: body functions and structures, activity and participation. Patient-centred outcomes were evaluated at 6 and 12 months: survival, hospitalisation, alive at home status and health-related quality of life. Pearson correlation, linear and logistic regression models were used to quantify associations of physical measures with patient-centred outcomes. Main results: No 6-month body functions and structures measure demonstrated consistent association with 6-month or 12-month outcomes in multivariable regression. The 6 min walk test, an activity measure, was associated with 6-month Short-Form 36 (SF-36) physical component scores (PCS, β range: 0.99 to 1.52, p<0.05). Participation measures (Functional Performance Inventory, FPI; Instrumental Activities of Daily Living, IADLs) were associated with SF-36 PCS (β range: FPI, 1.51–1.52; IADL, −1.88 to −1.32; all p<0.05) and Euro-QOL-5D utility score (β range: FPI, 2.00–3.67; IADL, −2.89 to −2.50; all p<0.01) at 6 and 12 months. Conclusions: Participation measures better reflect patient's quality of life than measures of body functions and structures within 12 months of ARDS among 6-month survivors, and are recommended for inclusion as a core measure in future studies.